Risk of childhood acute lymphoblastic leukaemia following parental occupational exposure to pesticides - Glass, D.; Reid, A.; Bailey, H.; Milne, E.; Fritschi, Lin (BMJ Group, 2012)
Objective: To ascertain whether there was an association between parental occupational exposure to pesticides and increased risk of acute lymphoblastic leukaemia (ALL) in the offspring. Method: A population-based case–control study of childhood ALL was conducted in Australia. Information about the occupational pesticide exposure of mothers and fathers was collected using job-specific modules. Information on the types and extent of pesticide exposure was collected for mothers and fathers before and around the time of conception, and also for mothers during pregnancy for the index case or control and for 1 year after birth. Results: Paternal occupational exposure to pesticides before or around conception was not related to increased risk of childhood ALL. There was a low prevalence of occupational exposure to pesticides among women that reduced after birth. Conclusions: Paternal occupational exposure to pesticides was not found to be associated with an increased risk of acute lymphoblastic leukaemia in the offspring. The study was underpowered with respect to maternal exposure to pesticides.